An experimental observation of the effects of submicron- and micron-sized mesoporous silica particles on the critical heat flux. (October 2020) - Lee, Min Suk; Kam, Dong Hoon; Jeong, Yong Hoon
Highlights: CHF experiments were conducted using mesoporous silica particles. Effects of particle size, particle shape, pore size, and concentration were observed. Increase and decrease of CHF were observed depending on particle size and pore size. Particles with small pores showed high CHF enhancement at high concentration. Abstract: Mesoporous particles have attracted attention for nuclear power plant systems, especially as part of a severe accident mitigation strategy to prevent the leakage of radioactive materials. For practical applications to nuclear systems, evaluations of the critical heat flux (CHF) is necessary to investigate the effects of mesoporous silica particles on the thermal safety margin. In this study, thus, pool boiling experiments were conducted using micron-sized porous silica particles to evaluate the effects of porous silica particle deposition on the CHF. Porous particles (0.5, 1, 2 μm) with pore sizes of 2 and 4 nm were prepared. Experiments were conducted under atmospheric pressure and low particle concentrations, ranging from 0.1 to 10 ppmv. Static contact angle measurements and Scanning Electron Microscopy (SEM) images were used for post-experimental surface analyses. As a result, unique CHF trends were observed as a function of the particle size, particle shape, pore size, and concentration. At relatively high concentration of 10 ppmv, CHF enhancement (up to 200 % of pure water) was observed for all particles, except for the 2 μm-sized particles with 4 nm of pores where CHF deterioration by 78 % of pure water was observed. In addition, at low concentration of 0.1 ppmv, CHF values appeared to be lower than those of pure water only for largest porous particles of 2 μm in diameter, not for amorphous ones. A new hypothesis was proposed to interpret the unique CHF trends considering microlayer evaporation theory, porous particle characteristics, and the effects on the particle deposition and the CHF.